Varietal identification in rice (Oryza sativa) through chemical tests and gel electrophoresis of soluble seed proteins - RAO, P S; BHARATHI, M; REDDY, K BAYYAPU; KESHAVULU, K; SUBBA RAO, L V; NEERAJA, C N (The Indian Journal of Agricultural Sciences, 2012)
Variety identification has great significance from seed production, breeding as well as intellectual property rights point of view to ensure quality seed. Forty varieties of rice were identified on the basis of seed colour (phenol, modified phenol and NaOH), seedling response (GA3 and 2, 4-D) to chemical tests and electrophoresis of soluble seed proteins (SDS-PAGE). Though no individual chemical test was able to distinguish all the genotypes, different chemical tests in conjunction were useful in identification of varieties. The SDS-PAGE of seed proteins was able to identify all the 40 genotypes of different origin and can be employed effectively for identification of these rice varieties. Dendrogram of the data indicated the wide diversity of the varieties released from Andhra Pradesh with similarity ranging from 0.36 to 0.98. Based on the response of 40 rice varieties to biochemical techniques and total soluble protein profiles through SDS- PAGE, a comprehensive ‘seed key’ has been developed for rapid varietal identification.